Transgenic Mice Overexpressing Human Alpha-1 Antitrypsin Exhibit Low Blood Pressure and Altered Epithelial Transport Mechanisms in the Inactive and Active Cycles - Liu, Lauren P.; Gholam, Mohammed F.; Elshikha, Ahmed Samir; Kawakibi, Tamim; Elmoujahid, Nasseem; Moussa, Hassan H.; Song, Sihong; Alli, Abdel A. (Frontiers in Physiology, 2021)
Human alpha-1 antitrypsin (hAAT) is a versatile protease inhibitor, but little is known about its targets in the aldosterone-sensitive distal nephron and its role in electrolyte balance and blood pressure control. We analyzed urinary electrolytes, osmolality, and blood pressure from hAAT transgenic (hAAT-Tg) mice and C57B/6 wild-type control mice maintained on either a normal salt or high salt diet. Urinary sodium, potassium, and chloride concentrations as well as urinary osmolality were lower in hAAT-Tg mice maintained on a high salt diet during both the active and inactive cycles. hAAT-Tg mice showed a lower systolic blood pressure compared to C57B6 mice when maintained on a normal salt diet but this was not observed when they were maintained on a high salt diet. Cathepsin B protein activity was less in hAAT-Tg mice compared to wild-type controls. Protein expression of the alpha subunit of the sodium epithelial channel (ENaC) alpha was also reduced in the hAAT-Tg mice. Natriuretic peptide receptor C (NPRC) protein expression in membrane fractions of the kidney cortex was reduced while circulating levels of atrial natriuretic peptide (ANP) were greater in hAAT-Tg mice compared to wild-type controls. This study characterizes the electrolyte and blood pressure phenotype of hAAT-Tg mice during the inactive and active cycles and investigates the mechanism by which ENaC activation is inhibited in part by a mechanism involving decreased cathepsin B activity and increased ANP levels in the systemic circulation.